Financial aspects of the use of locks and waterways in tourism. Example of a lock in Pakosc - Karczewska, Wiktoria; Gotowski, Rafał (Journal of Education, Health and Sport, 2019)
The lock in Pakość was built in 1882. Together with the lock in Łabiszyn they create a waterway called the Upper Noteć. In the builders assumption, the lock was part of a large hydrotechnical system that on the one hand, supplied the Bydgoszcz Canal with water, on the other hand it enabled inland navigation between Kruszwica, Inowrocław, Bydgoszcz and Nakło. Prime inland navigation in Pakość took place at the turn of the 19th and 20th centuries, the inter-war and postwar periods. Since the mid-seventies of the twentieth century, along with the development of motor transport, the increase in the size of inland ship, the lack of modernization works on locks leading to an increase in their dimensions and neglect on the shipping lane (no dredging works), freight shipping on the Upper Noteć River began to disappear and was replaced by tourist and recreation sailing.